(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2018)
Many economists believe that the development and promotion of small and medium-sized enterprises is one of the most important sources of economic and social development in countries in general and in developing countries in particular. This is considered to be an essential starting point for increasing production capacity and contributing to tackling poverty and unemployment. In view of the importance of these projects, most developing countries have concentrated their efforts on them. They have encouraged the establishment of small and medium industries, especially after they have proved their ability and efficiency in dealing with the major problems facing different economies. The banking system plays an important role by financing productive projects and increasing the substitution rates of local products instead of imported ones. This is achieved to achieve more than one objective. The first is achieving economic and national independence and abandoning dependency. Then building a solid production base that protects the country from international market fluctuations and increasing rates. Employment and unemployment control, reducing poverty, and building national technology.